Analisis Faktor Risiko Yang Mempengaruhi Terjadinya Karies Gigi Pada Anak Perempuan Kelas 3 Di SMPN 26 Palembang Tahun 2017 - Elya, Putri (Pengurus Daerah Ikatan Ahli Kesehatan Masyarakat (IAKMI) Provinsi Sumatera Selatan, 2018)
Caries is the main problem of oral health in children. Dental caries is a multifactorial disease as a result of the disturbed balance between the risk and protective factors. The aim of the present study was to analyze the risk factors for dental caries in female student at the goverment junior high school no. 26 Palembang. A cross-sectional dental caries examination and used total sampling forselected subject. Dental examinations based on DMFT index criteria and questionnaire surveys were performed on 114 children. All subjects have fully erupted permanent teeth and accepted as participants. The result of this study shows that there is a relationship between knowledge, maintenance of oral health, consumption of cariogenic foods, and UKGS. (p<0,05) with DMFT. It is suggested that the strict preventive and promotive programs should be implemented for decrease caries incidence rate and increase quality of life.